2021
DOI: 10.3390/jcm10040817
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interferon-Based Therapy on Hepatitis C-Associated Rheumatic Diseases: A Nationwide Population-Based Cohort Study

Abstract: Whether hepatitis C virus (HCV) infection-associated risk of rheumatic diseases is reversed by anti-HCV therapy remain elusive. A nationwide population-based cohort study of the Taiwan National Health Insurance Research Database was conducted. Of 19,298,735 subjects, 3 cohorts (1:4:4, propensity score-matched), including HCV-treated (6919 HCV-infected subjects with interferon and ribavirin therapy ≥ 6 months), HCV-untreated (n = 27,676) and HCV-uninfected (n = 27,676) cohorts, were enrolled and followed (2003–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
1
0
0
Order By: Relevance
“…A sustained virological response can be found in 40% to 80% of patients with HCV [ 27 , 44 ]. Our findings are consistent with those of a previous nationwide cohort study by Cheng et al [ 45 ], who reported that IBT could reduce the overall mortality in HCV-infected patients, but could not reverse HCV-associated risk of rheumatic diseases. A previous case–control study showed a controversial effect of IBT in SS patients with concurrent HCV [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…A sustained virological response can be found in 40% to 80% of patients with HCV [ 27 , 44 ]. Our findings are consistent with those of a previous nationwide cohort study by Cheng et al [ 45 ], who reported that IBT could reduce the overall mortality in HCV-infected patients, but could not reverse HCV-associated risk of rheumatic diseases. A previous case–control study showed a controversial effect of IBT in SS patients with concurrent HCV [ 28 ].…”
Section: Discussionsupporting
confidence: 93%